Does FinTech credit scale stimulate financial institutions to increase the proportion of agricultural loans? - Akm Mohsin; MD Rashidul Islam Sheikh; Hasanuzzaman Tushar; Mohammed Masum Iqbal; Syed Far Abid Hossain; Md. Kamruzzaman (Cogent Economics & Finance, 2022)
FinTech has raised the risk-taking level of financial institutions. This paper aims to explore FinTech Credit (FTC) scale of non-financial institutions and the risk-taking level of financial institutions into Opiela's model, constructs objective functions and constraints for representative financial institutions by conducting theoretical analysis and research hypothesis. It also explores the relationship between FTCscale and the proportion of agriculture-related loans. Based on the balanced panel data of 31 provinces and municipalities in China from 2009 to 2017, the individual fixed effects model is used to test the research hypothesis. Then, based on the balanced panel data of 31 provinces and municipalities in China from 2009 to 2017, the research hypothesis was tested using an individual fixed-effects model to explore the relationship between FTCscale and the proportion of agriculture-related loans. The results show that the FTCscale can increase the share of agriculture-related loans in financial institutions. Still, the percentage of agriculture-related loans and e-commerce factors increase at a marginal decreasing rate. Furthermore, the study shows that marketization and real estate development also indirectly affect the proportion of agricultural loans through the mediating part of the FTCscale. Finally, policy recommendations are proposed to develop FTC and the implementation of rural revitalization strategy.
Keywords: 330; FinTech credit; risk-taking level; agricultural loans; marketization level